Comparative transcriptomics and metabolomics provide insight into degeneration‐related physiological mechanisms of Morchella importuna after long‐term preservation - Ying Chen; Xuelian Cao; Liyuan Xie; Jie Tang; Lixu Liu; Di Wang; Xiang Wu; Tianhai Liu; Yang Yu; Yong Wang; Francis Martin; Weihong Peng; et al. (Microbial Biotechnology)
Abstract Ascomycetes fungi are often prone to degeneration. Agricultural production of the prized ascomycete mushroom Morchella importuna (black morel) typically suffers from reduced yield and malformed ascocarps owing to culture degeneration. This study compared M. importuna cultures subjected to five different long‐term preservation treatments, using transcriptomics and metabolomics. Avoiding repeated subculturing in combination with nutrient‐limited conditions was found to be the most beneficial method for maintaining the fruiting capability of morels. The expression of the gene sets involved in cysteine and methionine metabolism and nucleocytoplasmic transport was upregulated under nutrient‐limited and nutrient‐rich conditions, respectively. This increased expression was accompanied by differential accumulation of metabolites involved in nucleobase metabolism. Repeated subculturing triggered dissimilar changes in the functional modules under nutrient‐rich and nutrient‐limited conditions. A diverse set of cellular biochemical processes related to carbon metabolism were altered by repeated subculturing under nutrient‐rich conditions, whereas glycerophospholipid and purine metabolism were key functions affected by repeated subculturing under nutrient‐limited conditions. Altogether, metabolic alterations related to sulfur‐containing amino‐acid biosynthesis, DNA repair, and cellular structural maintenance contributed to improved preservation outcomes in terms of morel fruiting capability. Our findings contribute to a more detailed understanding of the molecular mechanisms related to subculturing and fruiting of ascomycete macrofungi after long‐term preservation.